Design and implementation of an IoT-based automatic package box security system with vibration sensors and GSM notifications using ESP32 - Fathahul Ammar Hasibuan; Firahmi Rizky (Lembaga Riset Mutiara Akbar, 2026)
The development of Internet of Things (IoT) technology has provided solutions to improve security systems, including securing package boxes from the risk of theft. This study aims to design and implement an IoT-based package box security system equipped with vibration detection features as an anti-theft system, automatic call notifications using a GSM module, and control and monitoring via a website. The research method used is the system design and development method which includes the hardware and software design stages, system implementation, and performance testing. The system was built using an ESP32 microcontroller integrated with a vibration sensor, buzzer, SIM800L GSM module, relay, solenoid door lock, and a website as a medium for remote monitoring and control. The results of the study show that the system is able to detect physical disturbances in the package box well through the vibration sensor. When vibrations exceed the threshold, the system activates an alarm and makes an automatic call to the user. The system is also able to display the status of the package box in real-time and provide open/close control via the website. Based on the test results, the system has an accuracy level above 90% with a fast response time.